Framing Positive Journalism in the Turkish President's Visit to Indonesia: Integration of Artificial Intelligence in Public Relations and Media - Saragih, M. Yoserizal (Indonesian Journal of Advanced Research, 2025)
The visit of the Turkish President to Indonesia is a diplomatic event that has attracted the attention of various national and international media. The study analyzes how the media frames these visits as well as how the integration of artificial intelligence (AI) can improve public relations strategies in journalistic reporting. Using Entman's framing analysis method and AI-based big data analysis approach, this study finds that the media's framing of diplomatic visits tends to be influenced by geopolitical interests and economic narratives. The study also shows that the application of AI in media analytics can help governments and public relations agencies understand news patterns and develop more effective communication strategies. The implications of this research contribute to the development of data-based journalism and digital public relations strategies in the context of global diplomacy.